Virtual regression-based myoelectric hand-wrist prosthesis control and electrode site selection using no force feedback. (April 2023) - Li, Jianan; Zhu, Ziling; Boyd, William J.; Martinez-Luna, Carlos; Dai, Chenyun; Wang, Haopeng; Wang, He; Huang, Xinming; Farrell, Todd R.; Clancy, Edward A.
Highlights: 1. Regression-based simultaneous, independent and proportional 2-DoF hand-wrist virtual myoelectric prosthesis control. 2. Automatic selectiion of best electrode sites based on backward stepwise selection. 3. Reduced calibration time with no force feedback needed.ss . Abstract: Most transradial prosthesis users with conventional "Sequential" myoelectric control have two electrode sites which control one degree of freedom (DoF) at a time. Rapid EMG co-activation toggles control between DoFs (e.g., hand and wrist), providing limited function. We implemented a regression-based EMG control method which achieved simultaneous and proportional control of two DoFs in a virtual task. We automated electrode site selection using a short-duration (90 s) calibration period, without force feedback. Backward stepwise selection located the best electrodes for either six or 12 electrodes (selected from a pool of 16). We additionally studied two, 2-DoF controllers: "Intuitive" control (hand open-close and wrist pronation-supination controlled virtual target size and rotation, respectively) and "Mapping" control (wrist flexion–extension and ulnar-radial deviation controlled virtual target left–right and up-down movement, respectively). In practice, a Mapping controller would be mapped to control prosthesis hand open-close and wrist pronation-supination. Eleven able-bodied subjects and 4 limb-absent subjects completed virtual target matching tasks (fixed target moves to a new location after being "matched, " and subject immediately pursues) and fixed (static) target tasks. For all subjects, both 2-DoF controllers with 6 optimally-sited electrodes had statistically better target matching performance than Sequential control in number of matches (average of 4–7 vs 2 matches, p  < 0.001) and throughput (average of 0.75–1.25 vs 0.4 bits/s, p  < 0.001), but not overshoot rate and path efficiency. There were no statistical differences between 6 and 12 optimally-sited electrodes for both 2-DoF controllers. These results support the feasibility of 2-DoF simultaneous, proportional myoelectric control.